ПЕДАГОГИКАЛЫҚ ИСКЕРЛИКТИ ЖЕТИЛИСТИРИЎДИҢ ЗАМАНАГӨЙ ТАЛАПЛАРЫ - Пирниязов, И.К. (ILIM hám JÁMIYET, 2019)
The article deals with the quality and effectiveness of teachers’training. The leading trends in the development of modern education are analyzed and it is emphasized the importance of introducing innovative technologies into the educational process, which are the main condition for ensuring high-quality educational results.